PENGARUH KARAKTER EKSEKUTIF, KARAKTERISTIK PERUSAHAAN, DAN DIMENSI TATA KELOLA YANG BAIK TERHADAP TAX AVOIDANCE DI BURSA EFEK INDONESIA (Pada Perusahaan Manufaktur Tahun 2011-2013) - Fitri Retno Dewy, 11.05.52.0077; Jaeni, Jaeni (Students Journal of Accounting and Banking, 2015)
The purpose of this study was to analyze the influence of corporate risk, size, leverage, sales growth, nol, multinational company, institutional ownership, the proportion of independent board, quality audit, the comite audit on the tax avoidance. The population of this research is manufacturing companies listed in Indonesian Stock Exchange in 2011-2013. The sampling technique used purposive sampling. Researchers used multiple regression to determine the relationship between these variables. The results showed that 47,6% of independent ability in explaining tax avoidance. Quality audits significant positive effect on tax avoidance. Corporate risk, leverage, nol and proportion of independent board significant negative effect on tax avoidance. While the size of the company, sales growth, multinational company, institutional ownership and audit committee has no effect on tax avoidance.Keywords: Risk, Size, Leverage, Sales Growth, NOL, Multinational Company, Institutional Ownership, The Proportion of Independent Board, Quality Audit, Audit Committee, Tax Avoidance